Imunoscintigrafie - Dolezal, J (Acta medica (Hradec Kralove). Supplementum, 1998)
Immunoscintigraphic methods present a great step forward in non-invasive diagnostics. They contribute not only in tumor diagnostic where monoclonal antibodies against tumorous antigens (TAG 72, CEA) are used but also in the sphere of inflammation diagnostic with the use of monoclonal antibody BW 250/183 which is bound onto non-specific cross reacting antigen NCA 95 of granulocytes. Another sphere of interest is the detection of heart muscle damage with the use of monoclonal antibody against myosin and detection of venous thrombosis with the use of monoclonal antibody against fibrin. Monoclonal antibodies are labelled with indium 111 or technecium 99m.
Keywords: Radioimmunodetection; monoklonální protilátky; radioimunodetekce; Antibodies, Monoclonal; Humans; lidé